1966
DOI: 10.1017/s0021859600068349
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between seed yield and associated characters in meadow fescue (Festuca pratensis)

Abstract: A study was made of phenotypic correlations between seed yield and some other traits of determinable value in two bred varieties of meadow fescue. Seed yield and such characters as time of flowering, plant height and dry-matter production of spaced plants in October and at the time of anthesis were found to be closely associated.The method of path coefficient analysis was used to study the interrelationships of seed yield and its components in the causal system: fertile tiller and floret numbers, percentage fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…In both field experiments on sowing rate, and also in each of the three sowing date experiments, seed yields per panicle in all treatments were similar and total seed yields depended greatly on panicle production. Several authors have reported the same close relationship between total production of inflorescences and seed yield (Langer, 1980;Nordestgaard, 1974;Stählin, 1972;Lewis, 1966). Hebblethwaite & Hampton (1981) compiled data from experiments with perennial ryegrass over 10 years and concluded that there is a weak correlation between seed yield and ear numbers, but a close relationship between yield and seed numbers per area.…”
Section: Inflorescence Production In Sowing Rate Experimentsmentioning
confidence: 88%
See 1 more Smart Citation
“…In both field experiments on sowing rate, and also in each of the three sowing date experiments, seed yields per panicle in all treatments were similar and total seed yields depended greatly on panicle production. Several authors have reported the same close relationship between total production of inflorescences and seed yield (Langer, 1980;Nordestgaard, 1974;Stählin, 1972;Lewis, 1966). Hebblethwaite & Hampton (1981) compiled data from experiments with perennial ryegrass over 10 years and concluded that there is a weak correlation between seed yield and ear numbers, but a close relationship between yield and seed numbers per area.…”
Section: Inflorescence Production In Sowing Rate Experimentsmentioning
confidence: 88%
“…The probable explanation for these conflicting findings is that yields of grass seed crops are mainly dependent on two components: the number of inflores cences per area, and floret utilization (i.e. the proportion of the florets that produc es harvestable seed) (Lewis, 1966;Griffiths, 1965). The other two yield-determin ing factors (floret number and seed weight) seldom give rise to considerable varia tions in yield.…”
Section: Inflorescence Production In Sowing Rate Experimentsmentioning
confidence: 99%
“…Several studies have been undertaken to determine the importance of seed yield components in grasses, e.g., Italian ryegrass (Bugge, 1981), perennial ryegrass Bugge, 1987), Kentucky bluegrass ( van Wijk, 1985), crested wheatgrass (Dewey & Lu, 1959), tall fescue (Nguyen & Sleper, 1983;Ibrahim & Frakes, 1984) and mead ow fescue (Lewis, 1966). When path analysis is applied, generally much variation in seed yield remains unexplained, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of seed production in perennial grasses have shown that fertility and number of fertile tillers are the main components determining seed yield (Griffiths 1965, Lewis 1966, Hill and Watkin 1975. The relative contribution of these components will be influenced by a number of other traits, e.g.…”
Section: Path Coefficient Analysismentioning
confidence: 99%
“…Meadow fescue is a tuft-growing perennial grass species, which has a wide range of distribution in the northern hemisphere (Hulte´n 1971). Systematic breeding of meadow fescue cultivars with improved forage yield and quality, and persistency, has been conducted since the middle of the last century (Lewis 1966, Simonsen 1975, 1977, Aastveit and Aastveit 1989, 1990, Casler and van Santen 2000, 2001. The lack of any deliberate breeding for seed productivity may be due to the thought that seed and forage production are negatively correlated (van Wijk 1980, Bugge 1987.…”
mentioning
confidence: 99%